EMPOWERMENT OF WOMEN ENTREPRENEURS IN THE HANDICRAFT INDUSTRY OF ASSAM AND THEIR ROLE IN PROMOTING SUSTAINABLE DEVELOPMENT - Boruah, Luna; Pathak, Vivek Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study looked at how women entrepreneurs in Assam's handicraft sector are empowered and how they contribute to sustainable development. A descriptive and exploratory study design was used to gather information from 150 female entrepreneurs in chosen districts via focus groups, interviews, and structured questionnaires. The results showed that most respondents felt more economically and socially empowered, as shown by higher incomes, more freedom to make their own decisions, and greater involvement in financial affairs. Additionally, a lot of business owners embraced eco-friendly methods including recycling waste and using locally sourced, eco-friendly products. Although the findings showed a clear connection between sustainability and women's empowerment, the study also noted some important drawbacks, such as limited social mobility and insufficient access to formal training. These observations underscore the necessity of focused policy assistance and capacity-building initiatives to enhance the contribution of female entrepreneurs to attaining equitable and sustainable growth in the handicraft industry of Assam.